The Role of Animal-Aided Design in Sustainable Architecture (International Journal of Built Environment and Sustainability, 2023)
Environmentally insensitive practices such as the unconscious use of natural resources, industrialization and unplanned urbanization cause the rapid destruction of natural habitats and even the extinction of some species. Today, as the importance of sustainable architecture has increased, architectural approaches that are compatible with nature have been adopted and thus the protection of natural life has been tried to be supported. As a definition, sustainability is a form of practice that aims to harmonize the built environment with natural life. In this context, the impact on animals whose habitats we are destroying is a significant topic within sustainability discussions. Studies show that the role and importance of human-animal based sustainable architectural habitats for enhancing animal welfare have not been extensively investigated. This study aims to discuss the importance of animal-aided designs within the sustainability approach. In addition, it is to carry out studies to improve the quality of life in society by strengthening the human-animal bond. In line with this purpose, animal-aided designs at urban, infrastructure, and building scales were analyzed within sustainability approaches, and their contribution to the sustainability approach was evaluated. As a result, it is emphasized that the sustainable animal-aided design approach provides innovative solutions for structures to be designed for animals and it also contributes to environmental, social, and economic sustainability, but in order for these designs to be successful, it is underlined that living spaces suitable for the needs of animals should be created and the negative effects of environmental impacts on animals should be considered. It is also emphasized that in addition to the principles of sustainability, factors that pay regard to the lives of animals contribute to the understanding of sustainability. It is expected that the discussion of the relationship between sustainability and animal-aided design, which is put forward through this study, will create an important discussion ground for future research and application examples.
Keywords: Sustainable architecture, Animal-aided design, Coexistence